2018
DOI: 10.1136/bmjresp-2017-000270
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial to compare the diagnostic yield of positron emission tomography CT (PET-CT) TARGETed pleural biopsy versus CT-guided pleural biopsy in suspected pleural malignancy (TARGET trial)

Abstract: IntroductionPleural malignancy, particularly malignant pleural mesothelioma (MPM) is increasing in incidence due to the long latency period from exposure to asbestos to development of the disease. MPM can be challenging to diagnose. For patients presenting without a pleural effusion, CT-guided biopsy remains the primary choice of biopsy, but the diagnostic sensitivity of this investigation is 70%–75%. Therefore, a proportion of patients will go on to require further biopsies. If the first biopsy is non-diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The TARGET study set out to specifically assess the role of PET-CT-guided biopsies in patients with ongoing suspicion of pleural malignancy despite a negative CT-guided biopsy. This was built on the premise that malignant pleural mesothelioma (MPM) in particular proves diagnostically challenging given its radiological appearance and the degree of overlap with benign pleural thickening [67]. Surprising to most pleural physicians and radiologists, their primary outcome of pleural malignancy correctly identified on 2 nd biopsy was not met (presented at BTS Winter 2019); however, the trial is still pending full publication and there is certainly more to learn from this.…”
Section: Ultrasound Vs Ct-guidedmentioning
confidence: 99%
“…The TARGET study set out to specifically assess the role of PET-CT-guided biopsies in patients with ongoing suspicion of pleural malignancy despite a negative CT-guided biopsy. This was built on the premise that malignant pleural mesothelioma (MPM) in particular proves diagnostically challenging given its radiological appearance and the degree of overlap with benign pleural thickening [67]. Surprising to most pleural physicians and radiologists, their primary outcome of pleural malignancy correctly identified on 2 nd biopsy was not met (presented at BTS Winter 2019); however, the trial is still pending full publication and there is certainly more to learn from this.…”
Section: Ultrasound Vs Ct-guidedmentioning
confidence: 99%
“…The TARGET trial (ISRCTN14024829) has been designed to investigate the role of PET/CT in suspected MPE by assessing whether targeted biopsy based on 18 FDG avidity improves diagnostic sensitivity over conventional CT-guided biopsy with the potential secondary benefit of identifying distant metastatic disease. This trial also aims to further clarify the role of serum mesothelin by including this biomarker in the assessment of subjects with mesothelioma (65).…”
Section: Imagingmentioning
confidence: 99%
“…However, the study by Yildirim et al reported high sensitivity, specificity, and accuracy (88.2%, 92.9%, and 90.3%, respectively) for differentiation of malignant mesothelioma from asbestos-related benign pleural disease in a group of 31 patients [ 89 ] evaluated by PET/CT. Similarly, Sun et al reported high sensitivity of 93% for FDG PET/CT in differentiating malignant from benign pleural effusion [ 90 ].The recent TARGET trial explores the potential role of FDG PET/CT to target areas of high uptake when performing a CT-guided biopsy [ 91 ].…”
Section: Pleuramentioning
confidence: 99%